Factors associated with Integrated Counselling and Testing Center (ICTC) service satisfaction: experience from Chandigarh, India - Devnani, Mahesh; Gupta, Anil Kumar; Wanchu, Ajay; Sharma, Rakesh K (Journal of College of Medical Sciences-Nepal, 2017)
Background & Objectives: People while availing services at Integrated Counselling and Testing Centers (ICTC) face a lot of administrative and procedural problems which affect their level of satisfaction. This study was conducted at ICTC, Post Graduate Institute of Medical Education and Research, Chandigarh; within the scope of a larger research evaluating the “Quality of Infrastructure and Services available to PLHA”; to analyze the user’s perception about quality of services and factors affecting satisfaction level. Materials & Methods: Exit interviews of 50 randomly selected ICTC clients were conducted with structured questionnaire containing five groups of questions and questions on waiting time and satisfaction level. A scoring system was devised. The satisfaction level was cross matched with group questions Results: The mean group scores of five groups of questions were: Information, access & guidance for services (42.5%), Behaviour of counsellors (94%), Quality of counselling (77.28%), Physical facilities (65.5%), Confidentiality, discrimination and grievance redressal (67%). All respondents said that counsellors were respectful and 91% found the behaviour of counsellor supportive & helpful, 80% reported that they understood everything that counsellor said. Eighty percent rated satisfaction level as satisfactory or above (6% very satisfactory, 74% satisfactory), 18% indifferent and 2% very dissatisfied. Factors found to be associated with client satisfaction level were counsellor’s response to the concerns and worries of clients up to their satisfaction (p=0.009), illumination in ICTC (p=0.04), knowledge of grievance redressal system (p=0.04) and total time spent in ICTC (p=0.03). Conclusion: This study provided user’s perspective about ICTC service and revealed the factors associated with ICTC service satisfaction level. Better quality ICTC Services can be provided by addressing these factors.